1998
DOI: 10.1074/jbc.273.30.18923
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and Lithium Interactions with the Na+/Dicarboxylate Cotransporter

Abstract: The two-electrode voltage clamp was used to study the currents associated with transport of succinate by the cloned Na ؉ /dicarboxylate cotransporter, NaDC-1, expressed in Xenopus oocytes. The presence of succinate induced inward currents which were dependent on the concentrations of succinate and sodium, and on the membrane potential. At ؊50 mV, the K 0.5 succinate was 180 M and the K 0.5 Na؉ was 19 mM. The Hill coefficient was 2.3, which is consistent with a transport stoichiometry of 3 Na ؉ :1 divalent anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(122 citation statements)
references
References 27 publications
11
109
1
1
Order By: Relevance
“…Furthermore, the present study shows that Li ϩ can substitute for Na ϩ , although to a small extent, in supporting succinate transport by NaDC3. Similar results have been obtained for rabbit NaDC1 (28). Thus, Li ϩ is a stimulator as well as an inhibitor for NaDC3 and NaDC1.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, the present study shows that Li ϩ can substitute for Na ϩ , although to a small extent, in supporting succinate transport by NaDC3. Similar results have been obtained for rabbit NaDC1 (28). Thus, Li ϩ is a stimulator as well as an inhibitor for NaDC3 and NaDC1.…”
Section: Discussionsupporting
confidence: 76%
“…These differences in K t values among NaDC1s from various animal species may not be entirely due to the differences in the experimental approaches employed in the determination of the K t values. A recent study (28) has shown that rabbit NaDC1 has a K t of 180 M in X. laevis oocytes when analyzed electrophysiologically, in contrast to the K t value of 25-30 M for rat NaDC1 obtained with similar experimental approaches (15,16). Therefore, the possibility of actual differences in the affinity of NaDC1 among various animal species cannot be ruled out.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, neither the cloned rabbit or human NaDC-1, nor X. laevis NaDC-2 were inhibited by dimethylsuccinate (13,14,18). Additionally, dimethylsuccinate did not evoke a significant current in oocytes injected with cRNA from rabbit NaDC-1 (35) or rat SDCT1 (16). The effect of cis-aconitate on the cloned luminal transporters has not been tested so far.…”
Section: Expression Cloning Of a Novel Na ϩ -Dicarboxylate Cotranspormentioning
confidence: 93%
“…Using the Michaelis-Menten equation, the best fit to the data could be obtained assuming a cotransport of 3 sodium ions, resulting in an apparent affinity constant of 39.6 Ϯ 3.3 mM Na brane depolarization and the inward current induced by succinate (not shown). The inhibition by lithium, which is probably due to the replacement of one of the sodium ions by lithium, has been shown previously for dicarboxylate transport in the renal luminal (33,34) and basolateral membranes (8,10), as well as for the cloned NaDC-1 of rabbit (13,35) and rat kidney (16). In contrast, lithium binds probably to all sodium binding sites of the intestinal transporter NaDC-2, albeit the V max of succinate uptake in the presence of Li ϩ was approximately one-third of that in the presence of Na ϩ (18).…”
Section: Functional Characterization Of Fnadc-3 By Uptake Studies Andmentioning
confidence: 99%
“…In contrast, 2,3-DMS was a very weak inhibitor of dicarboxylate transport at the luminal membrane (K i , 3.76 Ϯ 0.73 mM) (19). Within the cloned NaDC-1 orthologs, DMS analogs left either radiolabeled succinate uptake unaffected (41,45,46) or induced currents comparable in magnitude to succinate under two-electrode voltage clamp conditions (44,47,48). In contrast, NaDC-3 orthologs were generally sensitive to DMS analogs (12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 94%